Low-temperature ultra-high performance concrete and preparation method thereof

By using pumice stone with equal particle size distribution in low-temperature ultra-high performance concrete instead of fine sand aggregate, combined with the dense structure of ultra-high performance concrete, the problem of concrete structure damage in low-temperature environment is solved, significantly improving compressive strength and maintaining Stability of mechanical properties.

CN119263725APending Publication Date: 2025-01-07ZHONGSHAN ADVANCED ENG & TECH RES INST WUHAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411263907.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In low temperature environments, concrete structures lose their mechanical properties due to freezing stress damage. Although the addition of existing gas induction agents is relieved, it causes the skeleton structure to collapse before hardening, and the compressive strength decreases, making it difficult to ensure stability.

Method used

Pumice with equal particle size distribution is used to replace part of fine sand aggregate, combine with the dense skeleton structure of ultra-high performance concrete materials, regulate the composition of raw materials to reduce the damage to the matrix by freezing stress, and reduce the damage to the structure by low temperature through the porous properties of pumice.

Benefits of technology

It significantly improves the compressive strength of concrete at low temperatures, ensures the stability of mechanical properties, and alleviates the damage of freezing stress on the microstructure of the skeleton, ensuring structural integrity under constant low temperature environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263725A_ABST
    Figure CN119263725A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of concrete, and particularly relates to ultra-high-performance concrete capable of stably serving in a constant-low-temperature environment and a preparation method of the ultra-high-performance concrete. The invention provides ultra-high performance concrete, which is prepared from the following ingredients in parts by mass: 720 to 780 parts of cement, 180 to 220 parts of stone powder, 120 to 160 parts of silica fume, 450 to 790 parts of fine sand, 200 to 240 parts of coarse sand, 0 to 100 parts of pumice stone, 15 to 20 parts of water reducing agents and 180 to 200 parts of water. According to the low-temperature ultra-high-performance concrete prepared by replacing part of fine sand with the pumice, the addition amount of the gravel can be further reduced and the application efficiency of the pumice can be improved on the basis of ensuring stable improvement of mechanical properties under the action of constant low temperature and avoiding structural damage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and in particular relates to a low-temperature ultra-high performance concrete and a preparation method thereof. Background Art

[0002] The development of the permafrost environment requires that basic transportation facilities such as the Qinghai-Tibet Railway and the Sichuan-Tibet Railway need to cross plateau areas with permafrost environments. In the plateau area, the average annual temperature fluctuates between -10℃ and 5℃ all year round, and the average minimum temperature can even reach below -20℃. In addition, in the process of polar resource exploration, exploration infrastructure projects are gradually built in polar environments. Once completed, such buildings need to face a year-round low temperature environment. Among them, China's Antarctic Kunlun Station has a maximum temperature of only -10.4℃ in summer, a minimum temperature of -83.1℃ in winter, and an annual average temperature that fluctuates in the range of -52.5℃. Therefore, as a commonly used concrete material for infrastructure construction, it needs stable mechanical properties to face the year-round constant low temperature environment. Studies have pointed out that adding air-entraining agent to the matrix and introducing entrained air can alleviate the structural damage caused by hydrostatic pressure and ensure the stability of low-temperature performance. However, the addition of air-entraining agent will increase rapidly, causing the skeleton structure to collapse before hardening. The compressive strength decreases by about 7% with every 1% increase in air content. Before the low temperature effect, the structure has deteriorated and lost a lot of mechanical properties, making it difficult to ensure the stability of the later low-temperature service process. Therefore, ensuring the strength of the matrix skeleton structure while introducing entrained air is the key issue to solve the contradiction between antifreeze and structural enhancement in low-temperature environments.

[0003] Pumice is a natural sponge-like lightweight aggregate formed during the rapid cooling and solidification of molten lava (volcanic material). The porous structure of pumice is formed by millions of tiny voids or bubbles formed by trapping gases in the molten volcanic material during the cooling process. The air voids are parallel to each other, elongated, and sometimes interconnected, so pumice has the characteristics of high porosity, strong connectivity, low elastic modulus, and good frost resistance. Ultra-high performance concrete is a new type of concrete material with ultra-high strength and ultra-high durability. It has been applied to large-span bridge engineering, construction and transportation engineering, and marine engineering. Its excellent mechanical properties and durability are attributed to the most compact packing design of raw material compatibility. The matrix designed in this way has a dense skeleton structure to ensure the stable development of strength.

[0004] Therefore, pumice with porous characteristics is combined with ultra-high performance concrete with a high-strength skeleton structure, and the low-temperature ultra-high performance concrete with multiple low-temperature strength grades is produced by adjusting the raw material composition. Summary of the invention

[0005] The purpose of the present invention is to provide a low-temperature ultra-high performance concrete and a preparation method thereof. The low-temperature ultra-high performance concrete provided by the present invention introduces porous pores to reduce structural damage to concrete caused by low temperature on the basis of ensuring the integrity of the skeleton structure and the stable development of low-temperature mechanical properties.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a low-temperature ultra-high performance concrete, which comprises the following components in parts by mass:

[0008] 720-780 parts of cement, 180-220 parts of stone powder, 120-160 parts of silica fume, 450-790 parts of fine sand, 200-240 parts of coarse sand, 0-100 parts of pumice, 15-20 parts of water reducing agent and 180-200 parts of water.

[0009] The water-to-cement ratio of the low-temperature ultra-high performance concrete is 0.18.

[0010] Preferably, the cement comprises silicate cement with a particle size of 0.275 to 79.433 μm.

[0011] Preferably, the particle size of the stone powder is 0.363-13.183 μm.

[0012] Preferably, the particle size of the silica fume is 0.24-45.709 μm.

[0013] Preferably, the particle size of the fine sand is 0 to 0.6 mm.

[0014] Preferably, the particle size of the coarse sand is 0.6-1.25 mm.

[0015] Preferably, the pumice has a particle size of 0 to 0.6 mm, a porosity of 74.79%, and an apparent density of 1162.7 kg / m 3 , the saturated water absorption in deionized water is 94%.

[0016] Preferably, the mass ratio of the fine sand, coarse sand and pumice is 45-79:20-24:0-10.

[0017] The present invention also provides a method for preparing the low-temperature ultra-high performance concrete described in the above technical solution, comprising the following steps:

[0018] The components of the low-temperature ultra-high performance concrete are mixed, and are sequentially molded, cured and subjected to low-temperature treatment to obtain the low-temperature ultra-high performance concrete.

[0019] Preferably, the mixing comprises:

[0020] Firstly mixing cement, lime, silica fume, sand and pumice to obtain a premix;

[0021] The premix, water reducing agent and water are mixed for a second time to obtain slurry.

[0022] Preferably, the curing temperature is 18-22° C., and the relative humidity is ≥95%.

[0023] Preferably, the curing time is 3 days.

[0024] Preferably, the low temperature is -20°C or -80°C.

[0025] Preferably, the low temperature effect is characterized by a continuous constant low temperature effect.

[0026] The present invention provides a low-temperature ultra-high performance concrete, which includes the following components by mass: 720-780 parts of cement, 180-220 parts of stone powder, 120-160 parts of silica fume, 450-790 parts of fine sand, 200-240 parts of coarse sand, 0-100 parts of pumice, 15-20 parts of water reducer and 180-200 parts of water. The present invention uses pumice with equal particle size distribution to replace part of the fine sand aggregate. The low modulus and porous characteristics of pumice help to reduce the freezing stress caused by low temperature and the damage to the matrix skeleton structure. At the same time, with the help of the dense skeleton structure environment of the ultra-high performance concrete material, the pumice reduces the strength, so it can ensure the stability of the mechanical properties of the low-temperature ultra-high performance concrete under constant low temperature and alleviate the damage of the low-temperature freezing stress to the skeleton microstructure. . BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a morphological diagram of the internal pore structure of the pumice provided by the present invention.

[0028] Figure 2 This is a graph showing the compressive strength test results of low-temperature ultra-high performance concrete obtained in Examples 1 to 4 and Comparative Example 1.

[0029] Figure 3 This is the BSE diagram of Example 4.

[0030] Figure 4 This is the SEM image of Example 4.

[0031] Figure 5 This is the SEM image of Example 4. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention; it is obvious that the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments, and all other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making creative work are within the scope of protection of the present invention.

[0033] The present invention provides a low-temperature ultra-high performance concrete, which comprises the following components in parts by mass:

[0034] 720-780 parts of cement, 180-220 parts of stone powder, 120-160 parts of silica fume, 450-790 parts of fine sand, 200-240 parts of coarse sand, 0-100 parts of pumice, 15-20 parts of water reducing agent and 180-200 parts of water.

[0035] The water-to-cement ratio of the low-temperature ultra-high performance concrete is 0.18.

[0036] In the present invention, unless otherwise specified, all components are commercially available products well known to those skilled in the art.

[0037] The low-temperature ultra-high performance concrete provided by the present invention comprises 720 to 780 parts of cement, preferably 730 to 770 parts, and more preferably 740 to 760 parts by mass. In the present invention, the cement preferably comprises silicate cement. In the present invention, the particle size of the cement is preferably 0.275 to 79.433 μm. In the present invention, the cement has high strength and fast coagulation and hardening.

[0038] The low-temperature ultra-high performance concrete provided by the present invention comprises 180 to 220 parts of stone powder, preferably 190 to 210 parts by weight. In the present invention, the particle size of the stone powder is preferably 0.363 to 13.183 μm. In the present invention, the bonding strength of the stone powder is high. In the present invention, the stone powder can increase the nucleation effect of the hydration product and provide sites for the crystal nucleus.

[0039] The low-temperature ultra-high performance concrete provided by the present invention comprises 120 to 160 parts by mass of silica fume, and more preferably 130 to 150 parts. In the present invention, the particle size of the silica fume is preferably 0.24 to 45.709 μm. In the present invention, the activity of the silica fume is very high. In the present invention, the silica fume can fill the pores inside the concrete, and the active silicon dioxide can undergo a secondary reaction, thereby compacting the internal structure of the concrete.

[0040] The low-temperature ultra-high performance concrete provided by the present invention comprises 450 to 790 parts by mass, more preferably 460 to 780 parts by mass of fine sand; the particle size of the fine sand is preferably 0 to 0.6 mm.

[0041] In terms of mass fraction, the low-temperature ultra-high performance concrete provided by the present invention comprises 200 to 240 parts of coarse sand, and more preferably 210 to 230 parts; the particle size of the coarse sand is preferably 0.6 to 1.25 mm.

[0042] The low-temperature ultra-high performance concrete provided by the present invention comprises 0 to 100 parts by mass, more preferably 0 to 90 parts by mass of pumice; the particle size of the pumice is preferably 0 to 0.6 mm.

[0043] In terms of mass fraction, the mass ratio of fine sand, coarse sand and pumice in the low temperature ultra-high performance concrete provided by the present invention is 45-79:20-24:0-10, and more preferably 46-78::2-23:0-10. In the present invention, the sand particles with the above gradation ratio can make the materials closely stacked.

[0044] The low temperature ultra-high performance concrete provided by the present invention comprises 15 to 20 parts by mass of a water reducer, and more preferably 16 to 19 parts. In the present invention, the water reducer preferably comprises a polycarboxylate high efficiency water reducer.

[0045] The low-temperature ultra-high performance concrete provided by the present invention comprises 180 to 200 parts of water, more preferably 185 to 195 parts of water, in parts by mass.

[0046] The present invention also provides a method for preparing the low-temperature ultra-high performance concrete described in the above technical solution, comprising the following steps:

[0047] The components of the low-temperature ultra-high performance concrete are mixed, and are sequentially molded, cured and subjected to low-temperature treatment to obtain the low-temperature ultra-high performance concrete.

[0048] In the present invention, the mixing preferably includes:

[0049] Firstly mixing cement, lime, silica fume, pumice and sand to obtain a premix;

[0050] The premix, water reducing agent and water are mixed for a second time to obtain slurry.

[0051] In the present invention, the first mixing is preferably performed under stirring conditions; the stirring speed is preferably 130 to 140 rpm, more preferably 132 to 138 rpm, and more preferably 133 to 135 rpm; and the time is preferably 90 s.

[0052] In the present invention, the second mixing preferably includes sequentially performing a first slow stirring, a second slow stirring, standing and a fast stirring. In the present invention, the speed of the first slow stirring is preferably 130-140 rpm, and the time is preferably 60 s; the speed of the second slow stirring is preferably 130-140 rpm, and the time is preferably 120 s; the standing time is preferably 60 s; the speed of the fast stirring is preferably 275-285 rpm, and the time is preferably 60 s.

[0053] In the present invention, the mixing is preferably carried out in a stirring pot.

[0054] In the present invention, the forming preferably includes:

[0055] The mixed cement slurry is poured into a mold, compacted on a vibration table, and then the surface is scraped flat and coated, and then removed from the mold after being left at room temperature for 24 hours.

[0056] In the present invention, the curing temperature is preferably 18-22° C., more preferably 19-21° C., and more preferably 19-20° C.; the relative humidity is preferably ≥95%.

[0057] In the present invention, the curing age is preferably 3 days.

[0058] In the present invention, the low temperature action temperature is -20°C and -80°C.

[0059] In the present invention, the constant low temperature curing time is at least 1 day before the mechanical property stability monitoring is performed.

[0060] The present invention has no particular limitation on the curing process, and the curing process may be carried out using a process well known to those skilled in the art.

[0061] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0062] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0063] Examples 1 to 4 and Comparative Example 1

[0064] The original pumice is crushed and sieved, and the pumice with a particle size distribution of 0 to 0.6 mm is taken as an alternative aggregate to fine sand;

[0065] The low-temperature ultra-high performance concrete was prepared according to the raw material ratio in Table 1;

[0066] Put cement (particle size of 0.275-79.433 μm), stone powder (particle size of 0.363-13.183 μm), silica fume (particle size of 0.24-45.709 μm), pumice (particle size of 0-0.6 mm), fine sand (particle size of 0-0.6 mm) and coarse sand (0.6-1.2 mm) in a stirring pot, and stir at a speed of 130 rpm for 90 seconds to obtain a premix;

[0067] Add polycarboxylic acid water-reducing agent (solid content 35%) and water to the premix, stir at 130 rpm for 60 seconds, and after slurry is formed, stir at 130 rpm for 120 seconds, let stand for 60 seconds, and stir at 275 rpm for 60 seconds to obtain slurry.

[0068] The mixed slurry aggregate is poured into a mold, compacted on a vibration table and coated on the surface, and then removed from the mold after being left at room temperature for 24 hours;

[0069] The test blocks after demolding are placed in a standard curing room for curing, wherein the temperature of the curing room is 20±2°C, the relative humidity is ≥95%, and the curing age is 3 days. After standard curing for 3 days, the test blocks are placed in a constant low temperature refrigerator at -20°C and -80°C and frozen for at least 1 day to obtain the low-temperature ultra-high performance concrete.

[0070] Table 1 Raw material ingredients list of Examples 1 to 4 and Comparative Example 1

[0071]

[0072] Performance Testing

[0073] Test Example 1

[0074] The low-temperature ultra-high performance concrete obtained in Examples 1 to 4 and Comparative Example 1 was prepared into test pieces with a size of 40 mm × 40 mm × 160 mm, and the compressive strength was tested according to the "Test Method for Cement Mortar Strength (ISO Method)" (GB / T17671-2021). The compressive strength of Comparative Example 1 and Examples 1 to 4 after 3 days of standard curing, and the compressive strength after 1 day at a constant low temperature environment of -20°C and -80°C were tested respectively. The test results are shown in Table 2 and Figure 2 As shown. Among them, F0 is comparative example 1, F1 is embodiment 1, F2 is embodiment 2, F3 is embodiment 3, and F4 is embodiment 4. It can be seen from the test data that the mechanical property growth degree of the low-temperature concrete prepared by using pumice to replace part of the fine sand at constant low temperature is significantly higher than that of comparative example 1, and it can alleviate the damage of low-temperature freezing stress to the skeleton microstructure on the basis of ensuring a significant increase in compressive strength.

[0075] Table 2 Compressive strength of low temperature ultra-high performance concrete obtained in Examples 1 to 4 and Comparative Example 1

[0076]

[0077] Test Example 2

[0078] The low temperature ultra-high performance concrete obtained in Example 4 was subjected to scanning electron microscopy testing, and the obtained SEM image is as follows: Figures 3 to 5 As shown, Figure 3 is the BSE diagram of Example 4, Figures 4-5 It is the SEM picture of Example 4. Figures 2 to 5 It can be seen that the addition of pumice introduces a large amount of entrained air, which relieves the freezing stress under low temperature; at the same time, there is a large amount of dense CSH gel in the concrete matrix skeleton, which makes the structure of low-temperature ultra-high performance concrete dense and the compressive strength under constant low temperature is guaranteed.

[0079] The above is only a preferred specific implementation of the present invention; however, the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A low-temperature ultra-high performance concrete and a preparation method thereof, characterized in that: In parts by mass, it includes the following components: 720-780 parts of cement, 180-220 parts of stone powder, 120-160 parts of silica fume, 450-790 parts of fine sand, 200-240 parts of coarse sand, 0-100 parts of pumice, 15-20 parts of water reducing agent and 180-200 parts of water.

2. The low-temperature ultra-high performance concrete according to claim 1, characterized in that: The cement comprises silicate cement; the particle size of the cement is 0.275-79.433 μm, the cement has high strength and fast coagulation and hardening.

3. The low-temperature ultra-high performance concrete according to claim 1, characterized in that: The stone powder has a particle size of 0.363 to 13.183 μm, has high bonding strength, and can increase the nucleation effect of the hydration reaction to provide sites for crystal nuclei.

4. The low-temperature ultra-high performance concrete according to claim 1, characterized in that: The silica fume has a particle size of 0.24 to 45.709 μm and is highly active, and can fill the pores inside the concrete, so that the active silicon dioxide can undergo a secondary reaction to compact the internal structure of the concrete.

5. The low-temperature ultra-high performance concrete according to claim 1, characterized in that: The sand particles include fine sand and coarse sand; The particle size of the fine sand is 0 to 0.6 mm; The particle size of the coarse sand is 0.6-0.125 mm.

6. The low-temperature ultra-high performance concrete according to claim 5, characterized in that: The pumice aggregate is obtained by crushing and sieving large-size pumice. The particle size of the pumice selected after sieving is 0-0.6 mm, the porosity of the pumice is 74.79%, and the apparent density is 1162.7 kg / m 3 , the saturated water absorption in deionized water is 94%.

7. The low-temperature ultra-high performance concrete according to claim 6, characterized in that: The mass ratio of fine sand, coarse sand and pumice is 45-79:20-24:0-10.

8. A method for preparing low-temperature ultra-high performance concrete using any one of claims 1 to 7, characterized in that: The following steps are involved: The components of the low-temperature ultra-high performance concrete are mixed, and are sequentially molded, cured and subjected to low-temperature treatment to obtain the low-temperature ultra-high performance concrete.

9. The preparation method according to claim 8, characterized in that: The mixing includes: Firstly mixing cement, lime, silica fume, sand and pumice to obtain a premix; The premix, water reducing agent and water are mixed for a second time to obtain slurry.

10. The preparation method according to claim 8, characterized in that: The curing temperature is 18-22°C and the relative humidity is ≥95%; The curing time is 3 days; The low temperature is -20°C or -80°C; The low temperature effect is characterized by continuous constant low temperature effect.

Citation Information

Patent Citations

  • Pumice-based light self-compacting ultra-high-performance concrete and preparation method thereof

    CN110627429A

  • Low-temperature ultra-high performance concrete as well as preparation method and application thereof

    CN113061003A

  • Low-shrinkage high-crack-resistance ultra-high performance concrete and preparation method thereof

    CN113773018A

  • Cheap UHPC with Improved Properties

    KR102389372B1